Typification of three Rataj’s names in the genus Echinodorus (Alismataceae) - Somogyi, Jozef (Phytotaxa, 2019)
In 2017, notes on the nomenclature and taxonomy of some taxa of the genus Echinodorus described by Karel Rataj (1925–2014) were published by Somogyi (2017), including Echinodorus gabrielii Rataj (1990: 14–15), Echinodorus heikobleheri Rataj (2004: 33, 38–39, Fig. on the front side of the cover) (both of these names were neotypified) and Echinodorus multiflorus Rataj (1989: 23–25) (it was not possible to typify this name).